A copper based catalyst for poly-urethane synthesis from discarded motherboard. Issue 79 (10th August 2016) - Barman, Soumitra; Parasar, Bibudha; Kundu, Pradip; Roy, Soumyajit
Abstract : A cheap copper-based catalyst has been synthesized from discarded motherboard to replace the industrially used tin-based catalyst DBTDL and we found almost similar productivity. Abstract : By displaying thermoplastic, elastomeric and thermoset behavior depending on their chemical and morphological properties, polyurethanes have caught attention since 1937 when Bayer and his co-workers made them for the first time using the reaction of polyester diol and isocyanate. To produce a great range of versatility, various isocyanates can be used for making linear or cross-linked polyurethanes. Here we used IPDI as isocyanate and bamboo polyol as polyalcohol to prepare hard polyurethane and polyurethane foam. A cheap copper-based catalyst has been synthesized from discarded motherboard to replace the industrially used tin-based catalyst DBTDL [dibutyltin(iv ) dilaurate] which is expensive and we found almost similar productivity compared to conventional catalyst DBTDL. By optimizing catalyst loading, time and temperature, a 97% yield was obtained with 1.8 mol% catalyst loading in 2 hours. A plausible mechanism has also been proposed.